Murder In The Jungle: A Mystery Hounder Adventure - Sutapa Basu (Niyogi Books, 2024)
Evil is stalking the jungle. As tiger after tiger vanishes from Nagarhole wildlife reserve, despite sophisticated digital and human eyes on the ground, DFO Vinay Mishra and his team of forest officials are left puzzled. Also, what is the role of a Nawab, who is obsessed with history, in the midst of this mystery?
Keywords: Mystery -- Mystery